FERNANDES, Sueli. Educação de Surdos. Curitiba: Editora Ibepex, 2ª edição, 2011, 159 p. - Zilli, Arlete Gonçalves (Revista NEP - Núcleo de Estudos Paranaenses da UFPR, 2016)
FERNANDES, Sueli. Educação de Surdos. Curitiba: Editora Ibepex, 2ª edição, 2011, 159 p.